The mind-gut-immune connection : understanding how food impacts our mind, our microbiome, and our immunity - Mayer, Emeran A. (Harper , an imprint of HarperCollinsPublishers, 2023)
From one of today's leading experts on the emerging science of the microbiome comes a ground-breaking book that offers, for the first time, evidence that the gut-microbiome plays a pivotal role in the health crises of the twenty-first century.